Targeted Identification of Protein Interactions in Eukaryotic mRNA Translation. Issue 7 (3rd March 2020) - Link, Andrew J.; Niu, Xinnan; Weaver, Connie M.; Jennings, Jennifer L.; Duncan, Dexter T.; McAfee, K. Jill; Sammons, Morgan; Gerbasi, Vince R.; Farley, Adam R.; Fleischer, Tracey C.; Browne, Christopher M.; Samir, Parimal; et al.
Abstract: To identify protein–protein interactions and phosphorylated amino acid sites in eukaryotic mRNA translation, replicate TAP‐MudPIT and control experiments are performed targeting Saccharomyces cerevisiae genes previously implicated in eukaryotic mRNA translation by their genetic and/or functional roles in translation initiation, elongation, termination, or interactions with ribosomal complexes. Replicate tandem affinity purifications of each targeted yeast TAP‐tagged mRNA translation protein coupled with multidimensional liquid chromatography and tandem mass spectrometry analysis are used to identify and quantify copurifying proteins. To improve sensitivity and minimize spurious, nonspecific interactions, a novel cross‐validation approach is employed to identify the most statistically significant protein–protein interactions. Using experimental and computational strategies discussed herein, the previously described protein composition of the canonical eukaryotic mRNA translation initiation, elongation, and termination complexes is calculated. In addition, statistically significant unpublished protein interactions and phosphorylation sites for S. cerevisiae 's mRNA translation proteins and complexes are identified.